V-V Constructions in Sasaknese - Sartika Hijriati (Muhammadiyah University of Mataram, 2021)
The claim that serial verb constructions encode a single event is made with great regularity in the literature on serial verbs but is a claim that I find difficult to test in critical cases (Comrie, 1995). Sasaknese has a lot of serial verbs. This unique feature cannot be easily found in every language. This paper focused on analyzing the notion of ‘single-event’ in Sasaknese V-V constructions. In this study, the X-bar theory is applied to discuss the constituent structure of serial verb constructions. This study used the data of Sasaknese meno-mené native speakers’ utterances by using observation method. The result of the study shows that Sasak serial verb constructions have V-V structure that describe one single event as a single predicate